Toward a definition of excellence in classical arabic poetry: an analysis of Ibn Zaydūn's Nūniyya - Lug, Sieglinde (Journal of the American Oriental Society, 1981)
The present study of Ibn Zaydūn's Nūniyya is an attempt to contribute to recent analyses of classical Arabic literature in search of a new and more precise definition of the distinguished Arab poet. It demonstrates in detailed observations the special sensitivity of the poet Ibn Zaydūn in realizing the unique potential of the established classical forms. Elements like monorhyme, fixed meters, and well-known themes, which have often been criticized as stifling and monotonous, are employed so as to contribute in a crucial way to the total impression. The poet's mastery in attuning formal elements to the overall message endows them with suggestive power and poetic intensity. While many points on individual features may serve as an exposition of exemplary qualities applicable to classical Arabic poetry in general, the focus is on an integrated appreciation of the special poetic qualities of Ibn Zaydūn's Nūniyya.